2014
DOI: 10.1007/s10815-013-0152-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differing oocyte-secreted factors during mouse in vitro maturation on subsequent embryo and fetal development

Abstract: This study provides new knowledge on means to improve oocyte quality in vitro which has the potential to significantly aid human infertility treatment and animal embryo production technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 63 publications
6
51
0
Order By: Relevance
“…3). These results are entirely consistent with our recent observation that pro-BMP15, but not mature domain BMP15 nor mature domain mouse GDF9, enhances oocyte developmental competence (54,55). It is well established that prodomains of TGF-␤ superfamily growth factors have important roles in protein folding and regulation of bioactivity (56,57).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). These results are entirely consistent with our recent observation that pro-BMP15, but not mature domain BMP15 nor mature domain mouse GDF9, enhances oocyte developmental competence (54,55). It is well established that prodomains of TGF-␤ superfamily growth factors have important roles in protein folding and regulation of bioactivity (56,57).…”
Section: Discussionsupporting
confidence: 92%
“…We and others have shown that addition of "native" oocyte-secreted factors (e.g. pro-BMP15 or pro-GDF9) to IVM enhances oocyte quality, having profound effects on embryo development and fetal survival (13,54,55,(61)(62)(63)(64). This study is the first report on the effects of cumulin on oocyte quality.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, addition of a purified BMP15 pro-mature complex to IVM medium increases bovine embryo development [14], [38]. By contrast, we have recently shown that addition of the isolated mature homodomains of GDF9 and/or BMP15 (from R&D Systems) has no effect on mouse IVM [39]. No studies to date have directly compared the effect of the form of GDF9 or BMP15 added during IVM on embryo development.…”
Section: Introductionmentioning
confidence: 96%
“…Further, being bacterially expressed, this hGDF9 lacks the posttranslational modifications that may be relevant for GDF9 (66,72). Finally, the protein used for the above-mentioned granulosa cell studies consists of only the mature region of the protein, and we have recently shown that the purified mGDF9 mature region is not active in stimulating oocyte developmental competence (40). We have also shown for human BMP15 that the protein needs to be present as the purified pro-mature complex form to stimulate oocyte developmental competence (73).…”
Section: Discussionmentioning
confidence: 99%